Co0.85Se–Fe7Se8 nanocuboids embedded in reduced graphene oxides as cycle-stable anodes for sodium-ion batteries. (15th October 2022) - Wu, Han; Yuan, Ruilong; Li, Mengjun; Liu, Lei; Liu, Yuhang; Song, Qing; Ai, Wei; Du, Hongfang; Du, Zhuzhu; Wang, Ke
Abstract: The enhancement of the reaction kinetics and structural stability of transition metal selenides during the discharge-charge process remains a big challenge in realizing the further application of sodium-ion batteries (SIBs). Herein, we report a novel anode by strategically constructing the heterointerfaces in hollow Co0.85 Se–Fe7 Se8 nanocuboids uniformly dispersed on reduced graphene oxide (Co0.85 Se–Fe7 Se8 @rGO). The graphene decorated advanced hollow nanostructures could effectively buffer the volumetric stress and improve electrical conductivity. More importantly, by intelligently constructing heterostructures, a built-in electric field boosted on the heterointerface affords rapid ionic diffusion kinetics and improves electron transfer. With these merits, the Co0.85 Se–Fe7 Se8 @rGO anode exhibits a distinguished reversible capacity of 332.3 mAh g −1 at 0.1 A g −1 after 200 cycles, even retaining 300.8 mAh g −1 at 1.0 A g −1 after 1000 cycles. This work casts a new light on the smart design of metal selenide anode materials for SIBs. Graphical abstract: Long-term cycling performance of Co0.85 Se–Fe7 Se8 @rGO anodes at 1 A g −1 Image 1